Enhancing the Hydrogen Evolution Reaction Activity of Platinum Electrodes in Alkaline Media Using Nickel–Iron Clusters. Issue 27 (30th April 2020) - Xue, Song; Haid, Richard W.; Kluge, Regina M.; Ding, Xing; Garlyyev, Batyr; Fichtner, Johannes; Watzele, Sebastian; Hou, Shujin; Bandarenka, Aliaksandr S.
Abstract: Herein, we demonstrate an easy way to improve the hydrogen evolution reaction (HER) activity of Pt electrodes in alkaline media by introducing Ni–Fe clusters. As a result, the overpotential needed to achieve a current density of 10 mA cm −2 in H2 ‐saturated 0.1 m KOH is reduced for the model single‐crystal electrodes down to about 70 mV. To our knowledge, these modified electrodes outperform any other reported electrocatalysts tested under similar conditions. Moreover, the influence of 1) Ni to Fe ratio, 2) cluster coverage, and 3) the nature of the alkali‐metal cations present in the electrolyte on the HER activity has been investigated. The observed catalytic performance likely originates from both the improved water dissociation at the Ni–Fe clusters and the subsequent optimal hydrogen adsorption and recombination at Pt atoms present at the Ni–Fe/Pt boundary. Abstract : HER we go : An improved alkaline HER performance was achieved by modifying Pt(111) and nanostructured Pt electrocatalysts with nickel‐iron clusters. The activity was optimized by varying the Ni:Fe ratio, the coverage of the metal cluster, and the electrolyte composition. This improvement yields a more favorable balance between benefiting water dissociation and preventing *OH "poisoning".